Using Puppet Media in Improving the Speaking Ability of Junior High School Students 4 Waru Sidoarjo - Dwi Nur Hadiyansah (Universitas Pendidikan Mandalika, 2020)
To improve student achievement in EFL English, it was necessary and urgent to implement the model of innovative learning and constructive learning was through monologues that used this doll property. Property dolls were used to increase student motivation and provide a different atmosphere in learning to talk (speaking). Since all knowledge, dexterity, and skills had practical value. By obtaining the three men would more easily meet the desired of development. The important lesson here was not that we can achieve through the lesson. The subjects of this study were the 7th-grade student of Junior high school in Waru Sidoarjo. Classroom Action Research was designed in 2 cycles, respectively - each cycle consisting of the planning, execution, observation, and reflection. Research instrument and its action plan (teaching materials, observation sheets, and questionnaires) prepared by the researcher. The resulted in the first cycle based on observations. The evidence in the first cycle was not completed by 10 students or 25%, and a total of 30 students or 75%. These data show that the first cycle was not finished in the classical method as the standard was 85%. While the results of descriptive monologue presentations on the second cycle value - an average 81.75, while in the first cycle was 75.9. From these data, there was an increase of 5.85. Thus, the results obtained were consistent with the hypothesis proposed action, namely the use of appropriate doll media can improve the ability to speak in descriptive monologues for EFL.